AN ESTATE AGENT’S CLIENT FOR THE PURPOSES OF FICA - Henk Delport (Obiter, 2022)
The Financial Intelligence Centre Act 38 of 2001 (“FICA”) forms an integral part of the government’s strategy to combat money laundering. It establishes a statutory body called the Financial Intelligence Centre (“FIC”) and imposes a number of duties on certain institutions and persons (referred to in the Act as “accountable institutions”). Nineteen of these accountable institutions are listed in Schedule I to the Act, including attorneys, banks, public accountants, investment advisors, long-term insurers and estate agents.